PERANCANGAN BUKU KOMIK CERITA TRADISIONAL INDONESIA UNTUK REMAJA MODERN YANG TERBIASA DENGAN KOMIK JEPANG - Sheilen Wijaya; Shienny Megawati Sutanto (Universitas Ciputra Surabaya, 2016)
“The Legends” is a traditional comic book based on local fairytale and folklore in Indonesia. This research is done to create a comic book that will not only preserve the traditional Indonesian folklore, but also suit teenagers’ taste, especially female teenagers, that are already accustomed to reading Japanese comic books. In “The Legends” comic, the dress styles, characters’ names, architectures and some other aspects have been adapted to suit the taste of young readers that are accustomed to reading Japanese comic books. However, the moral and values will still be conveyed in the story to introduce Indonesian cultural values and moral to the readers. “The Legends” will be advertised through social media, which is one of the most effective ways to promote a product because it is accessible to visitors without time or distance constraints. Also, community events will be a suitable place to promote a product such as traditional comic book to target modern teen readers that are used to reading Japanese comic books.